(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The risks are considered as a large challenge facing the human communities. This challenge creates an economic and social burden which obstruct the community progress and influences on its evaluation in a negative way. In the last years, these risks began to increase and now it is necessary to face these risks in a regular and instructive methods in order to control over these risks and to limit its effects and reducing the losses, if it happened. The loss reduction and prevention programs produced by risks management are considered as a successful solution which enable to control these risks. These programs would not finish the danger in the community in a final way but it produces a practical solution reduces the negative effects and control it in a best way. Leaving the loss reduction and prevention programs means leaving things to time and co-incidence to take its course in any time and in any way. Loss reduction and prevention programs can be divided to: • Prevention programs reducing or defacing the opportunity of looses to take place. • Prevention programs reducing the losses sizeability if it happened. The programs in 1 will take it course before the risk happening, whether the second one after the risk takes place and the losses happening. Making decision using these programs depends on many factors and maybe the cost of using and applying these programs are the first factors .The reduction and prevention programs of reducing losses become one of the essential subjects in insurance and risk management for its benefits which reflecting positively on the community.